Comparison of parameters of the generalized extreme value distribution associated with extreme rainfall events in Central America - Guillén-Oviedo, Helen S.; Cid-Serrano, Luis R.; Alfaro-Martínez, Eric J. (Uniciencia, 2020)
The generalized extreme value distribution (GEVD) was used to model extreme rainfall events in Central America for a period of 30 years, beginning in 1971. Data consisted of daily rainfall records of 103 meteorological stations located throughout the isthmus. Central America was divided into 3 regions: Pacific, Caribbean and an intermediate zone. A bootstrap hypothesis test was used to compare the parameters of location, scale and form of the 3 regions. The results of the study showed significant differences between the 3 regions, mainly in terms of location and scale parameters.